Linking the cultural capital of the entrepreneur and early performance of new ventures: A cross-country comparison - Malgorzata A. Wdowiak; Erich J. Schwarz; Robert J. Breitenecker; Richard W. Wright (Journal for East European Management Studies, 2012)
We explore the impact of an entrepreneur's cultural capital on the performance of new ventures in both mature and transition economies. Results show that individualistic values of the founder influence early performance of new ventures, irrespective of the country context; and that in less advanced transition economies, the entrepreneur's cultural-background profile has a stronger influence on new venture performance than education or industry experience. Our findings support the assumption that entrepreneurial performance in new ventures is culture-driven, and suggest that economic analyses of entrepreneurial actions should encompass cultural values as well. – – In unserer Studie untersuchen wir den Einfluss des individuellen Kulturkapitals auf den Erfolg der Neugründungen in traditionellen und entstehenden Marktwirtschaften Europas. Die Ergebnisse zeigen, dass unabhängig vom Landeskontext individualistische Werte der Gründer den Unternehmenserfolg signifikant beeinflussen. In weniger fortgeschrittenen Transformationswirtschaften hat der kulturelle Hintergrund des ökonomischen Akteurs einen stärkeren Einfluss auf den Unternehmenserfolg als traditionelle Humankapitalgrößen wie Branchenerfahrung oder Ausbildung. Unsere Ergebnisse unterstützen die Annahme, dass der Erfolg von Neugründungen kulturell bedingt ist und dass diese Aspekte in die Entrepreneurship-Forschung besser integriert werden sollten.
Keywords: 650; entrepreneurship; new venture performance; cultural capital; transition economy; Slovenia; Poland; Austria